The family's experience of having a mentally ill family member - Margaret Ngqoboka; Antoinette Gmeiner; Marie Poggenpoel (AOSIS, 1998)
The purpose of this study was firstly to explore and describe the experience of families with a mentally ill family member and secondly to describe guidelines (based on the results obtained) for the advanced psychiatric nurse practitioner to assist families in mobilising their resources to facilitate the promotion, maintenance and restoration of their mental health as an integral part of health. Opsomming Die doel van hierdie studie was eerstens om die belewenis van gesinne wat 'n geestesongestelde gesinslid het, te verken en beskryfen in die tweede piek om riglyne te beskryfvir die gevorderde psigiatriese verpleegpraktisyn om hierdie gesinne the help in die mobilise ring van hulpbronne om hul geestes gesondheid as integrate deel van gesondheid te bevorder, te handhaaf en te herstel. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.